Will Artificial Intelligence for Drug Discovery Impact Clinical Pharmacology? - Zhavoronkov, Alex; Vanhaelen, Quentin; Oprea, Tudor I. (Clinical pharmacology and therapeutics, 2020)
As the field of artificial intelligence and machine learning (AI/ML) for drug discovery is rapidly advancing, we address the question “What is the impact of recent AI/ML trends in the area of Clinical Pharmacology?” We address difficulties and AI/ML developments for target identification, their use in generative chemistry for small molecule drug discovery, and the potential role of AI/ML in clinical trial outcome evaluation. We briefly discuss current trends in the use of AI/ML in health care and the impact of AI/ML context of the daily practice of clinical pharmacologists.